Jorvik calling - Dahlgren, Helena, 1980- (Dahlgren, Helena, 1980- Ödesyttarna., 2020)
"When Lisa and her dad arrive in Jorvik, she finds herself in a new city and at a new school trying to make new friends. This isn't the first time Lisa's moved because of her father's work, but this time it's without her mom. She died in a riding accident and Lisa hasn't gone near a horse since it happened. Despite her fears, it's not long before Lisa is drawn to the stables. To Linda, Alex, Anne, and to the horses. Especially one horse: Starshine. Everything is about to change for Lisa. Her love of horses is rekindled at the same time that she ends up in the middle of an ancient struggle between good and evil, and the legend of the Soul Riders ..."-- Provided by publisher.